Historiografia wobec poetyzacji słowa. Znaczenie literatury kontrfaktycznej dla popularyzacji wiedzy historycznej - Saja , Krystian (Przestrzenie Teorii, 2022)
The search for connections between history and literature has been going on continuously since antiquity. Interference between disciplines is obvious today, due to the narrative form of application, bringing the stories told closer to the novel. The search for non-narrative connections continues to this day. The main task of this article is to conduct a brief analysis of the basic interpretations of both disciplines and to indicate their role in building alternative literary stories. It also serves to show that categories such as narrative, imagery, truth and fiction play a pivotal role in the historiographic teaching process through alternative literary histories.